Widening the histopathological tool kit in clear cell odontogenic carcinoma for precision diagnostics - Ramya Ramadoss; Abigail Viola E; Chitra Shivalingam (Oral Oncology Reports)
Goal of the perspective: CCOC is a relatively uncommon malignant odontogenic tumor which presents with diagnostic challenges due to its perplexing histological patterns. It is critical to recognize this unusual tumor and distinguish it from other clear cell neoplasms in order to develop an effective treatment approach. Discussion: Tissue samples of clear cell odontogenic carcinoma were sourced from core, tumor permeated bone, semi permeated bone and unaffected bone. Validation with FT-IR revealed dominant phosphate in normal bone, increased amide groups in permeated bone and hydroxide group in core tissue. Conclusion: Routine histopathological assessment relies heavily on morphological alterations. Precise additional diagnostic tools like FTIR for effective ionic characterization are crucial to derive precision diagnostic and therapeutic strategies in lesions with enigmatic features.